Satisfaction, effectiveness, and usability of telerehabilitation for Parkinson's disease patients - Shohei Okusa; Hiroki Saegusa; Kazuya Miyakawa; Yuta Tsutsumi; Sae Ishida; Kyoko Nishikata; Tomonori Nukariya; Toshiki Tezuka; Yoshihiro Nihei; Yasuhiro Kitagawa; Shin-ichiro Kubo; Norihiro Suzuki; et al. (Journal of Rehabilitation Medicine)
Objective: To evaluate the satisfaction, effectiveness, and usability of a telerehabilitation programme for Parkinson’s disease (PD) patients.